TAX AGGRESSIVENESS: AN ANALYSIS OF THE EFFECTS ON THE PROFITABILITY OF COMPANIES UNDER JUDICIAL REORGANIZATION IN RIO DE JANEIRO - Andrade, Anderson Monteiro de (2021)
The present study aims to analyze the effects of tax aggressiveness on the profitability of Brazilian companies undergoing judicial reorganization. For this, we analyzed 360 annual statements of 138 companies that filed a request for judicial reorganization with the Tribunal de Justiça do Rio de Janeiro between 2017 and 2019. We used Effective Tax Rate (ETR) and Book-Tax Difference (BTD) as proxies for tax aggressiveness and Return on Asset (ROA) as a proxy for profitability. Additionally, we considered size and leverage as control variables. We used multiple linear regression for data analysis, applying the panel data model with fixed effects and quantile regression analysis. The results showed that, in general, the higher the level of tax aggressiveness, measured by the difference between accounting income and taxable income, the greater the profitability of companies undergoing judicial reorganization. Considering that this finding was more consistent for aggressiveness measured by the book and tax difference and that leverage demonstrated a relevant impact on profitability, this study aims to help companies undergoing judicial reorganization verify the trade-off between the costs and benefits generated by a more aggressive tax planning.